Tax-Favored Stock Donations by Corporate Insiders and Consequences for Equity Markets - Arya, Anil; Mittendorf, Brian; Ramanan, Ram N. V. (Management Science, 2022)
Although corporate insiders face substantial restrictions on stock sales, securing tax deductions through charitable donations of stock is viewed as an attractive alternative. Recent press coverage and growing empirical evidence confirm that insider donations occur frequently and often precede stock price drops. Securities regulators have also taken note, with a recent push for new rules to require rapid disclosure as with insider trades. This paper develops a model of informed stock trading when disposal of stock by insiders takes the form of tax-favored charitable donations rather than direct trading. We demonstrate that charitable gifts by insiders can reflect nonpublic information about firm value and that they do so in a manner that promotes greater market efficiency. Relative to informed trading, insider donations yield greater market liquidity, more efficient equity prices, and superior investor protection. The results suggest that although insider donations deserve scrutiny, they are not equivalent to insider trades. The results also provide a general framework to examine implications of insider donations for tax policy governing philanthropic behavior. This paper was accepted by Ranjani Krishnan, accounting. Supplemental Material: The e-companion is available at https://doi.org/10.1287/mnsc.2022.4514 .